Faktor-Faktor Penentu Nilai Perusahaan Pada Bank Umum Syariah di Indonesia Periode 2016-2020 - Anggreini, Gita Melliyani; Oktaviana, Ulfi Kartika (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2022)
This study aims to confirm whether internal factors are correlated to the firm value of Islamic commercial banks (BUS) in Indonesia, both partially and simultaneously. The Economic Value Added (EVA) method was adapted to measure firm value in the 2016-2020 period. The sample studied amounted to 11 BUS. The results of the study partially show that Operational Costs on Operating Income, Company Size, and Company Growth have a significant effect on the company value of Islamic commercial banks in Indonesia. On the other hand, Capital Adequacy Ratio, Non Performing Financing, Debt to Equity Ratio, Return on Assets, Operating Costs to Operating Income, Company Size, Company Growth and Institutional Ownership simultaneously affect the value of Islamic commercial banks in Indonesia. The variables of Capital Adequacy Ratio, Non Performing Financing, Debt to Equity Ratio, Return on Assets, Operational Costs to Operating Income, Company Size, Company Growth and Institutional Ownership are able to explain the influence of 46.9% on the value of Islamic commercial banks. While the remaining 53.1% is explained by the independent variables that are not examined.